A sampling method for estimating sporocarps production of wild edible mushrooms of social and economic interest - Ortega-Martínez, P.; Martínez-Peña, F. (Forest Systems, 2008)
This study introduces a new approach to determine and assess total mushroom production as well as to partitioning off this gross production into: non-harvested unripe production; non-harvested ripe production; harvested production; production eaten by fauna; and damaged production. Nine 300 m-long transects were established in the studied area. The sampling method was carried out in 2004, 2005 and 2006, but 2006 was the most productive year. In this year, a production of 5.37 kg/ha was estimated for Boletus edulis in 2006 of which 24% of Boletus edulis gross production was harvested, 26% was damaged and 15% was recorded as ripe production. The distribution of the gross production by classes permits knowing essential aspects regarding edible mushrooms management including which pressure is undergoing the fungal resource (due to harvesting or grazing), quantity and quality of the production or whether the species regeneration is guaranteed at any momenThis information allows us to ascertain the fungal resources conservation state and undertake a management and regulatory process for edible mushrooms in the sampled areas.